An accurate solution to the Lotka-Volterra equations by modified homotopy perturbation method - Chowdhury, Md. Sazzad Hossien; Rahman, M. M. (2011)

(untitled)
In this paper, we suggest a method to solve the multispecies Lotka-Voltera equations. The suggested method, which we call modified homotopy perturbation method, can be considered as an extension of the homotopy perturbation method (HPM) which is very efficient in solving a varety of differential and algebraic equations. The HPM is modified in order to obtain the approximate solutions of Lotka-Voltera equation response in a sequence of time intervals. In particular, the example of two species is considered. The accuracy of this method is examined by comparison with the numerical solution of the Runge-Kutta-Verner method. The results prove that the modi¯ed HPM is a powerful tool for the solution of nonlinear equations.